Congenital subcutaneous myofibroma: how to clinically exclude the diagnosis of infantile hemangioma. - Ingravallo, G.; Milano, A.; Lospalluti, M. (European Journal of Pediatric Dermatology, 2024)
Myofibroma is a rare benign tumor of myofibroblasts. The pediatric dermatologist may clinically suspect that it is not the much more frequent deep infantile hemangioma and must perform a biopsy, because only histological examination can easily clarify the diagnosis and differentiate it from other rare benign and malignant neoplasms of the newborn. Congenital myofibroma (CM) of the skin is most often isolated, but can present multiple cutaneous elements or also affect other organs, especially bones, central nervous system and lung. CM has a usually benign prognosis and tends to regress spontaneously, as can be seen when it is not completely removed and in multicentric forms. A case was described in a one-month-old baby girl and the clinical differential diagnosis from infantile hemangioma was discussed.